KOMPETENSI AWAL PESERTA DALAM MATA DIKLAT TEKNIK PRESENTASI BERBASIS MULTIMEDIA - Losarini Sumartati (Balai Diklat Keagamaan Bandung, 2019)
This study aims to determine the initial competency description of the functional training participants of the young teacher class XIII 2018. The research method used is descriptive method with a research instrument in the form of a closed questionnaire given to all training participants totaling 30 people, taking place on 9 October 2018. The distribution of questionnaires was conducted at the beginning of learning because it aims to find out the initial competency of the training participants before learning begins. The questions asked in this closed questionnaire are questions that must be answered by the training participants with answers